Advances in Computational Intelligence 15th International Work-Conference on Artificial Neural Networks, IWANN 2019, Gran Canaria, Spain, June 12-14, 2019, Proceedings, Part I - Rojas, Ignacio; Joya, Gonzalo; Catala, Andreu; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This two-volume set LNCS 10305 and LNCS 10306 constitutes the refereed proceedings of the 15th International Work-Conference on Artificial Neural Networks, IWANN 2019, held at Gran Canaria, Spain, in June 2019. The 150 revised full papers presented in this two-volume set were carefully reviewed and selected from 210 submissions. The papers are organized in topical sections on machine learning in weather observation and forecasting; computational intelligence methods for time series; human activity recognition; new and future tendencies in brain-computer interface systems; random-weights neural networks; pattern recognition; deep learning and natural language processing; software testing and intelligent systems; data-driven intelligent transportation systems; deep learning models in healthcare and biomedicine; deep learning beyond convolution; artificial neural network for biomedical image processing; machine learning in vision and robotics; system identification, process control,and manufacturing; image and signal processing; soft computing; mathematics for neural networks; internet modeling, communication and networking; expert systems; evolutionary and genetic algorithms; advances in computational intelligence; computational biology and bioinformatics.
Machine learning in weather observation and forecasting -- Computational intelligence methods for time series -- Human activity recognition -- New and future tendencies in brain-computer interface systems -- Random-weights neural networks -- Pattern recognition -- Deep learning and natural language processing -- Software testing and intelligent systems -- Data-driven intelligent transportation systems -- Deep learning models in healthcare and biomedicine.
Keywords: Bioinformatics; Artificial intelligence; Computer vision; 9; Algorithms; Data protection; Computational and Systems Biology; Artificial Intelligence; Computer Vision; Computer Communication Networks; Algorithms; Data and Information Security